2017
DOI: 10.1016/j.jacep.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Evaluation of Major Adverse Events After Catheter Ablation for Atrial Fibrillation

Abstract: CA is a relatively safe procedure with low incidence of major AEs. The incidence of procedure-related CVA appeared to decline significantly over time. Incidence of PERD remained relatively stable and was more likely to be diagnosed after discharge and following repeat CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
18
1
Order By: Relevance
“…Although prior evaluations of the incidence of major AEs in AF patients who underwent CA included a low proportion of patients with comorbid HF (0.4% to 18%), the incidence of major AEs between 1% and 6% did not differ from the present study which only included patients with comorbid HF . Only two studies indicated that HF was a predictor for major AEs (univariate HR 5.2 [95% CI, 2.0‐13.4]); however, the comparable incidence between the present study and the safety evaluations of all AF patients undergoing CA seems to indicate no increase in AE risk with the addition of HF.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Although prior evaluations of the incidence of major AEs in AF patients who underwent CA included a low proportion of patients with comorbid HF (0.4% to 18%), the incidence of major AEs between 1% and 6% did not differ from the present study which only included patients with comorbid HF . Only two studies indicated that HF was a predictor for major AEs (univariate HR 5.2 [95% CI, 2.0‐13.4]); however, the comparable incidence between the present study and the safety evaluations of all AF patients undergoing CA seems to indicate no increase in AE risk with the addition of HF.…”
Section: Discussioncontrasting
confidence: 81%
“…Advanced age has consistently been identified as a predictor of major AEs amongst patients undergoing CA, regardless of the presence of HF . Coronary artery disease, however, was only identified as predictive of hemorrhage complications in Bertaglia et al (OR, 5.6 [95% CI, 1.6‐20.1]).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations